Perancangan Jemuran Otomatis Berbasis Arduino Uno (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Ongoing global warming makes the seasons in Indonesia irregular. These uncertain conditions will be very inconvenient if you want to dry clothes. This worry increases when the house is empty, while the clothesline that is used to dry wet clothes is still outside the house so that the clothes that are being dried in the sun do not dry as optimally. The research method that will be implemented in this research is Prototype. The author designed an automatic clothesline using an Arduino Uno-based microcontroller and a rain sensor with a miniature minimalist house. people do not need to manually pick up clothes that are drying in the sun when the weather conditions are rainy. Because the to designed by the author is able to secure clothes automatically when it's raining. The rain sensor used can detect rain conditions, so it can protect clothesline. The design of an automatic clothesline with a miniature minimalist house, which was made in this study, is the answer to problems that often occur in society.